„TRESHOLD OF MEANING“ AND „CEILING OF FORM“ IN THE CONTEMPORARY MILITARY - Stanar, Dragan (National interest, 2023)
In this paper author wishes to explore and investigate the relationship between form and meaning in contemporary militaries, aiming to identify the phenomena of form not reaching the threshold of meaning and form which breaks its own ceiling. Relying on methods of conceptual analysis, comparative analysis, content analysis, deduction and other scientific methods, the author identifies the problematic phenomena of form not meeting the threshold of meaning and form which breaks its own ceiling. These are the cases of misunderstanding, or even deliberate ignoring, of the value nature of form, which is always and by definition in the realm of instrumental, and even postulating form as an intrinsic value, a value in itself. When form has no contribution to achieving a goal of intrinsic and “final” value, then it cannot be observed as valuable, and as such it loses its existential justification. Moreover, in cases in which form becomes observed as intrinsic value, i.e., not an instrument and means of achieving some final value, but rather a value in itself, it breaks its own proverbial ceiling. Both these cases are hindering, even detrimental, to achieving the final goal on the basis of which they were even created in the first place. The author first explains why form is of such crucial value for the military, as it is extremely complex and “unnatural,” observing several aspects of the military which demand the existence of strict and robust form in order for the system to properly function. Upon explaining its significance, the author identifies specific articulations of form – previously elaborated phenomena of form aren’t reaching the threshold of meaning and for breaking its own ceiling – which are detrimental to the military. The author argues that such articulations of form are not in military systems. At the same time, that they are extremely dangerous and detrimental for optimal functioning of the military. In conclusion of the paper, the author asserts that certain measures must be implemented in military systems. They must evaluate and re-evaluate all existing articulations of form to identify and eliminate those which have no justification for existence. Such evaluation must be undone in an ad hoc fashion, but rather a process of constant evaluation of form must be integrated into the military organization to yield optimal results.